2014
DOI: 10.1007/s11746-014-2563-6
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Sensitive Adhesives Based on Oleic Acid

Abstract: Existing pressure sensitive adhesives (PSA) are mostly based on petrochemical‐based polymers. This study reveals a new class of bio‐based polymers that can be used as PSA. The polymers are hydroxyl‐containing polyesters from the step‐growth polymerization of epoxidized oleic acid (EOA), an AB‐type monomer containing both a carboxylic acid group (A) and an epoxy group (B). The monomer is derived from epoxidation of renewable methyl oleate followed by selective hydrolysis of the ester group. The polymers (PEOA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…By exploiting these functional groups, vegetable oils have been successfully used as renewable starting materials for the preparation of a large variety of monomers and polymers . Some fields of application include epoxy resins, polyurethane resins, and pressure‐sensitive adhesives …”
Section: Introductionmentioning
confidence: 99%
“…By exploiting these functional groups, vegetable oils have been successfully used as renewable starting materials for the preparation of a large variety of monomers and polymers . Some fields of application include epoxy resins, polyurethane resins, and pressure‐sensitive adhesives …”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of the polymerization with FTIR also revealed that the epoxy groups were consumed faster than the -COOH groups throughout the polymerization, which suggested that the epoxy groups also reacted with other functional groups in addition to the -COOH groups. The other functional groups might include the newly generated hydroxyl groups and water (13,14,17). The tacky film from the DA-TMPGE mixture on the PET backing exhibited a peel strength of 1.2 N/cm and a shear strength of more than 240 h (Table 1, entry 5).…”
Section: Scheme 1 Proposed Polymerization Of Da and A Difunctional Omentioning
confidence: 99%
“…It has also been reported that PSAs can be developed from the curing of polyesters from the condensation of dimer acid (DA) and diols with epoxidized plant oils (10,11). PSAs can also be developed from the polymerization of an AB-monomer, epoxidized oleic acid (12,13). It has been demonstrated that a mixture of epoxidized fatty acids (EFAs) can be efficiently produced from the selective hydrolysis of epoxidized soybean oils (14).…”
Section: Introductionmentioning
confidence: 99%
“…[ 17,28 ] In addition, hydroxyl-containing polyesters were obtained via step-growth polymerization of epoxidized oleic acid and showed adequate adhesion but low molecular weights. [ 29 ] Wool and co-workers endeavored the design of PSA copolymers based on the fatty acid methyl ester. In their work, acrylated methyl oleate (AMO) was polymerized using emulsion and miniemulsion polymerization techniques.…”
Section: Introductionmentioning
confidence: 99%